Antifungal Activity of Chitosan Nanoparticles and Correlation with Their Physical Properties - Ling Yien Ing; Noraziah Mohamad Zin; Atif Sarwar; Haliza Katas (International Journal of Biomaterials)
The need of natural antimicrobials is paramount to avoid harmful synthetic chemicals. The study aimed to determine the antifungal activity of natural compound chitosan and its nanoparticles forms against Candida albicans, Fusarium solani and Aspergillus niger. Chitosan nanoparticles were prepared from low (LMW), high molecular weight (HMW) chitosan and its derivative, trimethyl chitosan (TMC). Particle size was increased when chitosan/TMC concentration was increased from 1 to 3 mg/mL. Their zeta potential ranged from +22 to +55 mV. Chitosan nanoparticles prepared from different concentrations of LMW and HMW were also found to serve a better inhibitory activity against C. albicans (MICLMW=0.25–0.86 mg/mL and MICHMW=0.6–1.0 mg/mL) and F. solani (MICLMW=0.86–1.2 mg/mL and MICHMW=0.5–1.2 mg/mL) compared to the solution form (MIC=3 mg/mL for both MWs and species). This inhibitory effect was also influenced by particle size and zeta potential of chitosan nanoparticles. Besides, Aspergillus niger was found to be resistant to chitosan nanoparticles except for nanoparticles prepared from higher concentrations of HMW. Antifungal activity of nanoparticles prepared from TMC was negligible. The parent compound therefore could be formulated and applied as a natural antifungal agent into nanoparticles form to enhance its antifungal activity.